Draft Sikkim Statistical Supplement for Annual Plan 1994-95 (Volume II) - Planning Commission (Planning Commission, 1994)
Summary Statement, Agriculture Soil & Water Conservation Animal Husbandry & Veterinary Services Fisheries Forest & Wildlife Cooperation Rural Development/Special Programme Rural Development Community Development & Panchayat Land Reforms Irrigation and Flood Control.
Planning & Development Department, Government of Sikkim Gangtok